Mithras Clark hotel and casino - Santos, Noelle Paola N.
The national and local tourism plans for Clark were to develop a mixed-use tourism complex and a new market-competitive destination respectively. In addition to this, one of the goals identified by Central Luzon, in the aspect of tourism, was to elevate the region from being, just a gateway to an inviting tourism destination. These recognized challenges led to the design problem and that was to create a mixed-use tourism facility that would improve Clark's tourism industry and help the region to becoming an inviting tourism destination. Furthermore, with the strengthening of the hotel and casino industry in Clark, proved by the location of the future hotel and casino strip in its Long-Term Development Plan, the booming M.I.C.E. industry based on the previous events in Clark, and the evaluation of the existing leisure facilities in Clark, these essential factors reinforced the idea of the type of mixed-use tourism facility to be designed: an integrated hotel, casino, retail and function facility. The concept was anchored to what Clark was really known for, a former military airbase. Being the logistics hub during Vietnam War, it hosted F-4 Phantom II Jets, and this military unit being of significance to Clark for the 88 years that it had been an airbase was used as the design concept. The result of this thesis is, Mithras, named after one of the initial name schemes for Phantom II jets, an integrated hotel, casino, retail and function facility strategically located at the corner of Clark's two major avenues and future hotel and casino strip. It is set to be the largest hotel in Clark with its 500 guest rooms and suites, offering the biggest casino and accommodation for functions, events, and celebrations in Clark, and boasting multi-levels of high-end retail stores. Over-all it aims to provide a luxurious experience to its customers with its sophisticated design, extensive range of facilities and state-of-the art amenities.